Kinetic and sensory analysis of ginger beer produced by diversified fermentation methods - Alencar, Erika Magalhães; Souza, Antonia Queiroz Lima de; Perdigão, Lourdes Mylla Rocha; Santos, Wenderson Gomes dos (Revista de Ciências Agroveterinárias, 2025)
This study investigates the production of ginger beer flavored with soursop, highlighting its viability in the fermented beverage market and its connection to Brazilian biodiversity. The research focused on the physicochemical, microbiological, and sensory characterization of the beverage, comparing induced and natural fermentation, with and without the use of ginger bug. The results indicate that the addition of ginger bug increased the alcohol content of the fermented beverage to 0.71 °GL, while fermentation without ginger bug showed no detectable alcohol. On the other hand, induced fermentation resulted in an alcohol content of 4.32 °GL. Microbiological analyses confirmed the absence of coliforms and pathogens, ensuring compliance with quality standards. In sensory evaluation, the fermented beverage with 20% soursop received the highest flavor ratings (above seven), while the same concentration in natural fermentation had the lowest acceptance in purchase intent. These data suggest that ginger beer can be a viable and healthy alternative in the market for fermented beverages, leveraging the richness of Brazilian biodiversity.